Change Processes and Future Perspectives in the Knowledge Society. The Example of Clothing and Textile Industry - Woll, Tobias (2008)
The paper examines change processes und future perspectives in the knowledge society. It presents the clothing and textile industry as an example for a transforming industry in a global economy. The paper reviews existing future studies, which have surveyed change processes and future developments in the clothing and textile industry. Main goals of the review are the identification of changes in work and the description of the restructuring of global value chains within the clothing and textile sector. The paper also highlights major current trends, drivers of change and future prospects in this sector.